2016
DOI: 10.1246/cl.160216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Magnetic Properties of Linear Two-coordinate Monomeric Diaryliron(II) Complexes Bearing Fused-ring Bulky “Rind” Groups

Abstract: Monomeric diaryliron(II) complexes, Fe(Rind) 2 , have been obtained by introducing fused-ring bulky "Rind" groups. For Fe(Eind) 2 , a significant orbital contribution of the Fe(II) ion due to the linear two-coordination has been determined by the highly effective magnetic moment (® eff = 5.82 ® B ) and the extraordinarily large internal hyperfine field (H n = ca. 140 T) in the Mössbauer spectrum. Variable-frequency out-of-phase ac susceptibility data demonstrate an effective spin-reversal barrier of U eff = 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Complexes with a 3d 8 configuration, in particular iron­(II), were among the first MX 2 complexes reported to show slow magnetic relaxation, and their electronic structure and magnetic anisotropy have been studied thoroughly. It was shown by ab initio analysis that changes in the ligand environment have little effect on the 5 Δ ground state as the orbital contribution | M L | = 2 remains largely unquenched in all cases …”
Section: Introductionmentioning
confidence: 99%
“…Complexes with a 3d 8 configuration, in particular iron­(II), were among the first MX 2 complexes reported to show slow magnetic relaxation, and their electronic structure and magnetic anisotropy have been studied thoroughly. It was shown by ab initio analysis that changes in the ligand environment have little effect on the 5 Δ ground state as the orbital contribution | M L | = 2 remains largely unquenched in all cases …”
Section: Introductionmentioning
confidence: 99%
“…We have focused on the synthesis and magnetic properties of the Rind-substituted diorganoiron(II) compounds, Fe(Rind) 2 . 50 The treatment of FeCl 2 (thf ) 1.5 with 2 equiv of (Rind)Li has resulted in the formation of discrete molecules of Fe(Rind) 2 as an air-sensitive compound. Figure 17 shows the structure of Fe(EMind) 2 determined by X-ray crystallography, demonstrating the almost linear structure with CFeC = 178.0 (1) We have isolated some mixed diorganocopper(I) species by introducing the bulky Rind groups, as shown in Scheme 16.…”
Section: Organo-transition Metal Complexesmentioning
confidence: 99%
“… The readily available Rind groups have several advantages over the existing bulky aryl groups, as represented by the versatility and size-controllability by the introduction of a variety of R-substituents at the four benzylic positions in the rigid s -hydrindacenyl skeleton. We have already found that the Rind groups can stabilize some reactive species of the main group elements as well as transition metals. For example, recently we reported the synthesis of a size-selected gold cluster, Au 41 [S­(Eind)] 12 , and a redox-active [Fe 4 S 4 ] 3+ cluster, [Fe 4 S 4 {S­(Eind)} 4 ] − , using a bulky Rind-based thiol, (Eind)­SH.…”
Section: Introductionmentioning
confidence: 99%